Analysis of soil organic matter in tropical soils with near-infrared spectroscopy (NIRS) and chemometrics - Jarquín-Sánchez,Aarón (Pontificia Universidad Católica de Chile. Facultad de Agronomía e Ingeniería Forestal, 2012)
The objective of this study was to predict the concentration of soil organic matter (SOM) in tropical soils using near-infrared spectroscopy (NIRS) for samples measured within a polyethylene bag and without a bag. One hundred and fifty six soil samples from the humid tropics of Tabasco, Mexico with contrasting chemical characteristics were selected. The samples were dried, ground, and sieved through 2 mm and 5 mm screens, and their SOM contents were determined using the Walkley-Black method. The soil samples were packed in polyethylene bags, and SOM was measured directly with and without a bag using a quartz probe (FOSS 5000 model of NIRsystems, DK-3400 Hillerod,Denmark) for a range from 1100 to 2000 nm to obtain a prediction model of SOM. The model for determining SOM for bagged samples had good fit and explained 88% of the variation (0 to 10, 2% of SOM of samples). The model for determining SOM for bag-less samples was not efficient for predicting independent samples and therefore was discarded. The analysis by NIRS was reliable, more rapid, and easier for the determination of SOM in soil samples measured through a plastic bag.